Family Centeredness in Mental Health: A Concept Analysis - Iril Panes (San Beda University, 2020)
Background: Mental illness affects the entire family structure. The family members are the main provider of care that results in caregiving burden. Thus, the care given should encompass the entire family system, termed as family centeredness. Purpose: This study clarifies the concept of "family centeredness" in mental health to enhance individual and family cares living amid mental illness. Methods: This research employed Walker and Avant's method of Concept Analysis. Literature was reviewed, and the characteristics that appeared repeatedly were noted and categorized. Data were mapped according to its definition, antecedents, attributes, and consequences. Results: Three key defining attributes were identified: (a) A mutual, collaborative partnership between the patient, family and health care providers based on knowledge exchange, open communication and cooperation; (b) A supportive, professional relationship/bond/engagement among health care providers, patient and family characterized by empathy, understanding, respect and empowerment; and (c) Individualized care wherein the process is defined by the family is supported, enabling the opportunity to choose, control over decisions and empowerment. Conclusion: The result of the study clearly defines family centeredness as a health care approach in mental health that acknowledges the patient and family as the experts on themselves, involves families as collaborative partners in all aspects of services and decisions about care through mutually beneficial supportive partnerships with health care providers; to help patients make progress towards recovery.